A Fluorescent Adenosine Analogue as a Substrate for an A‐to‐I RNA Editing Enzyme1. (10th June 2015) - Mizrahi, Rena A.; Shin, Dongwon; Sinkeldam, Renatus W.; Phelps, Kelly J.; Fin, Andrea; Tantillo, Dean J.; Tor, Yitzhak; Beal, Peter A.
Abstract Adenosine to inosine RNA editing catalyzed by ADAR enzymes is common in humans, and altered editing is associated with disease. Experiments using substrate RNAs with adenosine analogues at editing sites are useful for defining features of the ADAR reaction mechanism. The reactivity of ADAR2 was evaluated with RNA containing the emissive adenosine analogue thieno[3, 4‐d]‐6‐aminopyrimidine (thA). This nucleoside was incorporated into a mimic of the glutamate receptor B (GluR B) mRNA R/G editing site. We found that thA is recognized by AMV reverse transcriptase as A, and is deaminated rapidly by human ADAR2 to give thI. Importantly, ADAR reaction progress can be monitored by following the deamination‐induced change in fluorescence of the thA‐modified RNA. The observed high thA reactivity adds to our understanding of the structural features that are necessary for an efficient hADAR2 reaction. Furthermore, the new fluorescent assay is expected to accelerate mechanistic studies of ADARs.